Persepsi Masyarakat Nelayan mengenai Pendidikan di Desa Paluh Kurau, Hamparan Perak, Deli serdang - Agung Suharyanto; Devi Annisa Siagian; Juanda Juanda; Supriadi Putro Panjaitan; Syafriyeni Tanjung; Toho C.M Situmorang (Universitas Negeri Medan, 2017)
The perception of fishermen about formal education is influenced by various factors, both internal and external factors. The perception someone has is different from the perception of others. Based on this the researcher in this case found that the views of parents of children's education in Hamlet 14 Village Paluh Kurau Kec. Silver Overlay Kab. Deli Serdang varies. From the data obtained from the parents in Dusun 14 Desa Paluh Kurau Kec. Silver Overlay Kab. Deli Serdang said that, firstly education is important, they always tell and do not forbid their children to go to school, it's just that sometimes their children do not want to go to school. Second, parents are still more concerned with the economy, it is evidenced by how to include children in terms of making a living. This happens because parents have experienced it from previous generations. This situation is in perparah with the behavior of children in line with the old opinion where the school was not so important.